2019
DOI: 10.1101/849240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interneuron dysfunction in a new knock-in mouse model of SCN1A GEFS+

Abstract: Advances in genome sequencing have identified over 1300 mutations in the SCN1A sodium channel gene that result in genetic epilepsies. However, how individual mutations within SCN1A produce seizures remains elusive for most mutations. Previous work from our lab has shown that the K1270T (KT) mutation, which is linked to GEFS+ (Genetic Epilepsy with Febrile Seizure plus) in humans, causes reduced firing of GABAergic neurons in a Drosophila knock-in model. To examine the effect of this mutation in mammals, we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…However, it remains unclear how most individual mutations in SCN1A lead to seizures. Recent studies have identified a significant depolarizing shift in action potential threshold in parvalbumin expressing inhibitory hippocampal CA1 interneurons but not in firing properties of excitatory pyramidal neurons, suggesting that mutations in the same gene on different cells may cause different consequences (Das et al, 2021). Thus, if single-cell sequencing developed in recent years is used in the future, it will help to identify more specific molecules and also to explain shared mechanisms of different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear how most individual mutations in SCN1A lead to seizures. Recent studies have identified a significant depolarizing shift in action potential threshold in parvalbumin expressing inhibitory hippocampal CA1 interneurons but not in firing properties of excitatory pyramidal neurons, suggesting that mutations in the same gene on different cells may cause different consequences (Das et al, 2021). Thus, if single-cell sequencing developed in recent years is used in the future, it will help to identify more specific molecules and also to explain shared mechanisms of different diseases.…”
Section: Discussionmentioning
confidence: 99%